Poverty and Inequality in Tunisia: Recent Trends - Deeksha Kokas; Abdel Rahmen El Lahga; Gladys Lopez-Acevedo (Institute of Labor Economics (IZA), 2021)
Tunisia's reforms and agile shift to a more democratic political system since a major political revolution in 2011 has not prevented continued and rising citizen discontent. While this paper does not directly analyze this vexing problem, it assesses welfare indicators and labor markets nationally, regionally, and across different population groups—such as women and youth—over the last two decades. The paper shows that while Tunisia has significantly reduced poverty between 2000 and 2019, the profile of the poor has not changed much: poverty remains concentrated in rural and western regions, mainly among households with younger men without education and headed by someone working in low-productivity sectors such as agriculture and construction. Moreover, the share of the vulnerable Tunisian population at risk of falling into poverty is quite large, especially after the COVID-19 pandemic, even though poverty had been declining over the past two decades. Non-monetary dimensions of well-being, such as access to basic services, are also unevenly distributed across regions and population groups. COVID-19 has further aggravated these disparities and is reversing Tunisia's poverty reduction gains. The paper sheds light into the issues that require policy attention on poverty.
Keywords: J31; F16; 330; poverty; inequality; Tunisia